PERTUMBUHAN DUA JENIS CACING TANAH DALAM MEDIA LIMBAH PELEPAH SAWIT DENGAN KOTORAN AYAM - Dini Nuraini; Yusfiati '; Herman ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Earthworms have characteristic and a different range of tolerance to environmental conditions such as pH and soil organic content. The purpose of this study was to determine the growth of earthworm Perionyx sp1 (worm milk) and Perionyx sp2 (red worm) in waste of the oil palm frond with chicken manure media. The parameters measured were body weight, number of coccoons produced, temperature and soil pH. The eksperiment were designed using factorial completely randomized with 5 treatment and 3 replications. The data were analysz using (ANOVA) with DMRT at 5% significant. The results showed that earthworm weight and the number of coccoon was significantly different at treatment media (P> 0.05). The traetment with 75% of oil palm fronds waste and 25% chicken manure were the best media to increased body weight and the number of coccoons for both earthworm.